The day the king died : a terrible miscarriage of justice - Morris, Jim (Waterside Press, 2015)
There was a quaint British convention under which executions were stopped and sentence commuted if scheduled to take place on the day the sovereign died. Alfred Moore was doubly unfortunate: still protesting his innocence he was on the scaffold an hour before the death of King George VI was announced.